2014
DOI: 10.1097/hcr.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Illness Behavior After Cardiac Surgery

Abstract: Gender differences exist in denial, disease conviction, and dysphoria, probably depending on the culturally assigned roles of men and women. As these aspects of IB may compromise treatment compliance and the quality of life, the efficacy of cardiac rehabilitation programs might be improved taking into account the different prevalences in men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…22 Reports of differences in physical function, favoring men, have also been reported in the general cardiac surgical literature. 29, 30 Differences in anxiety/depression by gender are also supported by the literature, early and later after heart transplantation, 26, 31, 32 after cardiac surgery, 33, 34 and in patients with heart failure. 35 Our findings suggest an opportunity to focus attention on subgroups of patients to maximize HRQOL before and after device implantation.…”
Section: Discussionmentioning
confidence: 53%
“…22 Reports of differences in physical function, favoring men, have also been reported in the general cardiac surgical literature. 29, 30 Differences in anxiety/depression by gender are also supported by the literature, early and later after heart transplantation, 26, 31, 32 after cardiac surgery, 33, 34 and in patients with heart failure. 35 Our findings suggest an opportunity to focus attention on subgroups of patients to maximize HRQOL before and after device implantation.…”
Section: Discussionmentioning
confidence: 53%
“…Being male was a significant predictor of increased anxiety. Modica et al (19) found that the different ways in which male and female cardiac patients frequencies and percentages their disease may be related to the outcomes of a CR program. They pointed out that men use denial mechanisms significantly more often than women do.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the number of the men who considered at least one uncontrollable biological risk factor as the cause of their disease was threefold that of the women. This is while based on a study by Modica et al (2014), there is a significant difference between men and women in terms of coping with a cardiac condition after surgery. In other words, men resort to the denial mechanism significantly more commonly than women when contending with a cardiac condition following surgery, which can affect the result of a cardiac rehabilitation program (16).…”
Section: Discussionmentioning
confidence: 99%
“…This is while based on a study by Modica et al (2014), there is a significant difference between men and women in terms of coping with a cardiac condition after surgery. In other words, men resort to the denial mechanism significantly more commonly than women when contending with a cardiac condition following surgery, which can affect the result of a cardiac rehabilitation program (16). In fact, the denial of the current situation by men is followed by treatment resistance, with its corollary impact on the anxiety scores in different ways.…”
Section: Discussionmentioning
confidence: 99%